The ambiguous embrace : government and faith-based schools and social agencies - Glenn, Charles Leslie, 1938- (New forum books., 2000)
"Glenn builds a case for faith-based organizations playing a far more active role in American schools and social agencies. He shows that they could do so both while receiving public funds and while striking a workable balance between accountability and autonomy."--Jacket